Synthesis and antibacterial activity of novel 3-O-arylalkylcarbamoyl-3-O-descladinosyl-9-O-(2-chlorobenzyl)oxime clarithromycin derivatives. Issue 20 (1st November 2018) - Qin, Yinhui; Qiang, Shengsheng; Ji, Shengli; Liu, Zhiyang; Hu, Chaoyu; Ma, Shutao
Graphical abstract: Highlights: Novel 3-substituted derivatives of clarithromycin were synthesized and evaluated. Some of them showed potent activity against both susceptible and resistant strains. Compound7z exhibited potent and balanced antibacterial activity. Abstract: A novel series of 3- O -arylalkylcarbamoyl-3- O -descladinosyl-9- O -(2-chlorobenzyl)oxime clarithromycin derivatives, were designed, synthesized and evaluated for their in vitro antibacterial activity. These derivatives were found to have strong activity against susceptible and resistant bacteria strains. Among them, compounds7a and7q showed the most potent activity (0.125 µg/mL) against erythromycin-resistant S. pneumoniae expressing the mef A gene. Moreover, compounds7f, 7i, 7p and7z displayed remarkably improved activity (4 µg/mL) against penicillin-resistant S. aureus ATCC31007, and compounds7a, 7b, 7f, 7p and7z showed improved activity (8 µg/mL) against erythromycin-resistant S. pyogenes . In particular, compound7z exhibited potent and balanced activity against the tested drug-susceptible and -resistant bacterial strains.